Dairy goat milking : handbook for farmers: a step by step guide - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2018)
This handbook seeks the outline standard operating procedures for each step of the value chain to ensure the production of a high quality finished product. It can also serve as a practical guide to farmers, processors and consumers when producing, handling and consuming goat's milk.